Berberine was neuroprotective against an in vitro model of brain ischemia: Survival and apoptosis pathways involved - Simões Pires, Elisa Nicoloso; Frozza, Rudimar Luiz; Hoppe, Juliana Bender; Menezes, Bruna de Melo; Salbego, Christianne Gazzana (Brain research, 2014)
Berberine is an alkaloid derived from herb the Berberis sp. and has long-term use in Oriental medicine. Studies along the years have demonstrated its beneficial effect in various neurodegenerative and neuropsychiatric disorders. The subject of this study was to evaluate whether berberine protects against delayed neuronal cell death in organotypic hippocampal culture (OHC) exposed to oxygen and glucose deprivation (OGD) and the cell signaling mechanism related to its effect. Hippocampal slices were obtained from 6 to 8-days-old male Wistar rat and cultured for 14 days. Following, the cultures were exposed for 1h to OGD and then treated with Berberine (10 and 20μM). After 24h recovery, propidium iodide (PI) uptake was analyzed and a decrease was observed in PI uptake on OGD Ber-treated culture, which means a decrease in cellular death. Western blot analysis showed that proteins Akt, GSK3β, ERK and JNK appear to play a role in berberine-mediated neuroprotection. Furthermore, capase-3 activity of OGD Ber-treated culture was diminished by control level in a fluorimetry assay. These findings suggest that berberine-mediated neuroprotection after ischemia involves Akt/GSK3β/ERK 1/2 survival/apoptotic signaling pathway as well as JNK and caspase-3 activity inhibition. •Berberine treatment was neuroprotective against brain ischemia in vitro model.•Berberine treatment after OGD acted on Akt, GSK-3β, and ERK 1/2 and JNK signaling.•Berberine also ameliorates caspase-3 activity after OGD.